Characteristics of Environmental Klebsiella pneumoniae and Klebsiella oxytoca Bacteriophages and Their Therapeutic Applications - Beata Weber-Dąbrowska; Maciej Żaczek; Małgorzata Łobocka; Marzanna Łusiak-Szelachowska; Barbara Owczarek; Filip Orwat; Norbert Łodej; Aneta Skaradzińska; Łukasz Łaczmański; Dariusz Martynowski; Marta Kaszowska; Andrzej Górski (MDPI AG, 2023)
In recent years, multidrug-resistant (MDR) strains of Klebsiella pneumoniae have spread globally, being responsible for the occurrence and severity of nosocomial infections. The NDM-1-kp, VIM-1 carbapenemase-producing isolates as well as extended-spectrum beta lactamase-producing (ESBL) isolates along with Klebsiella oxytoca strains have become emerging pathogens. Due to the growing problem of antibiotic resistance, bacteriophage therapy may be a potential alternative to combat such multidrug-resistant Klebsiella strains. Here, we present the results of a long-term study on the isolation and biology of bacteriophages active against K. pneumoniae, as well as K. oxytoca strains. We evaluated biological properties, morphology, host specificity, lytic spectrum and sensitivity of these phages to chemical agents along with their life cycle parameters such as adsorption, latent period, and burst size. Phages designated by us, vB_KpnM-52N (Kpn52N) and VB_KpnM-53N (Kpn53N), demonstrated relatively broad lytic spectra among tested Klebsiella strains, high burst size, adsorption rates and stability, which makes them promising candidates for therapeutic purposes. We also examined selected Klebsiella phages from our historical collection. Notably, one phage isolated nearly 60 years ago was successfully used in purulent cerebrospinal meningitis in a new-born and has maintained lytic activity to this day. Genomic sequences of selected phages were determined and analyzed. The phages of the sequenced genomes belong to the Slopekvirus and Jiaodavirus genus, a group of phages related to T4 at the family level. They share several features of T4 making them suitable for antibacterial therapies: the obligatorily lytic lifestyle, a lack of homologs of known virulence or antibiotic resistance genes, and a battery of enzymes degrading host DNA at infection.